The Entertaining Way to Behavioral Change : Fighting HIV with MTV - Banerjee, Abhijit (World Bank, Washington, DC, 2019)
This paper tests the effectiveness of an entertainment education television series, MTV Shuga, aimed at providing information and changing attitudes and behaviors related to HIV/AIDS. Using a simple model, the paper shows that “edutainment” can work through an individual or a social channel. This study is a randomized controlled trial conducted in urban Nigeria, where young viewers were exposed to MTV Shuga or a placebo television series. Among those exposed to MTV Shuga, the trial created additional variation in the social messages they received and the people with whom they watched the show. The study finds significant improvements in knowledge and attitudes toward HIV and risky sexual behavior. Treated subjects are twice as likely to get tested for HIV eight months after the intervention. The study also finds reductions in sexually transmitted diseases among women. These effects are stronger for viewers who reported being more involved with the narrative, consistent with the psychological underpinnings of edutainment. The trial’s experimental manipulations of the social norm component did not produce significantly different results from the main treatment. The individual effect of edutainment thus seems to have prevailed in the context of this study.